Optimisasi Program Linear Pada Permasalahan Multikriteria Menggunakan Metode ε-constraint - Purba, Switamy Angnitha; Afandi, Trisno; Fadhillah, Dinda Rizka; Wahyuni, Sri; Januarti, Ria (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2023)
The purpose of this study is to solve multi-criteria problems using the ε-constraint method with the help of an excel solver. The multi-criteria optimization problem is an optimization problem that has more than one objective function. A multi-criteria optimization problem can be said to be a multiple criteria decision making (MCDM) if there is more than one thing that must be considered in the model as a goal or criterion. In general, the weighting method and the Îµ-constraint method are the most widely used. The weighting method converts a set of options into options by multiplying each option by the inventory weight. On the other hand, the Îµ-constraint method only saves one of the existing goals and limits the goals with a certain number of values to get an efficient limit.